Pelaksanaan Pull Marketing Jokowi Ahok dalam Pemenangan Pemilukada DKI Jakarta 2012 - IQBAL, LALU MUHAMMAD (Komunikator, 2013)
The victory of Jokowi-Ahok in 2012 Jakarta Governor Election was the result of integrated political marketing activity with prominent pull marketing factor. Jokowi-Ahok utilized optimally the power of media which is very effective in providing information for the people of Jakarta. This study aims to observe how far pull marketing was used with other elements. In political marketing, there are nine elements which become the important parts. One of these nine important elements is pull marketing, which has a significant role for Jokowi-Ahok. Based on the analysis of the data, it shows that pull marketing strategy was the strategy which was mainly used. The use of media in Jakarta Governor Election was an important instrument in succession of regional leaders, in addition to the mass mobilization supported by political parties and sympathizers. Based on result of data processing, it shows that pull marketing strategy worked quite effectively. The combination of media, figures, and campaign methods was then mixed into strategic moves that made Jokowi-Ahok surpass all their competitors. Keywords: Pull Marketing, Media, Governor Election